Gubernur Jenderal Hindia-Belanda dan Kebijakannya pada Tahun 1900-1945 serta Kondisi Sosial, Budaya dan Ekonomi - Ira Sugiarnik (SINDANG: Jurnal Pendidikan Sejarah dan Kajian Sejarah, 2022)
The Dutch East Indies government itself is an extension of the Dutch kingdom. In moving the government every day the Governor General is Followed by an Institution Named the Algemeene Secretariat, a special institution in the governorate, specifically dealing with correspondence policies that will be issued by the Dutch East Indies government. Colonial administration is dualistic, it means that there are two layers, the background of the emergence of this dualistic government is actually still related to the implementation of the culture which in this practice really requires cooperation with local aristocrats, another goal of implementing this dualistic system as the main tool in maintaining conditions colonialism, especially regarding the interests of the mother country in this colonized land. Under the authority of the governor general of the Dutch East Indies at that time, there was an assumption that all existing affairs and problems could be handled properly if decentralization was implemented. Decentralization itself is a consequence of the Ethical Policy which was heavily campaigned at the end of the 20th century. The implementation of this decentralization eventually led to the formation of regional councils. One of the forms of the decentralization law was the formation of the People's Council or Volksraad on May 18, 1918, to be precise during the governor general van Limburg Styrum.